Severe Acute Respiratory Syndrome Type 2‐Causing Coronavirus: Variants and Preventive Strategies (Adv. Sci. 11/2022). Issue 11 (14th April 2022) - Aydogdu, Mehmet Onur; Rohn, Jennifer L.; Jafari, Nazila V.; Brako, Francis; Homer‐Vanniasinkam, Shervanthi; Edirisinghe, Mohan
Abstract : Covid‐19 Variants and Prevention Preventive strategies such as vaccines, repurposed drugs and physical‐materials science based scenarios to create vectors interacting with SARS‐CoV‐2 to tackle the spread of the virus and its various mutations have been an exceptional addition to humanity's arsenal to cope with the ongoing Covid‐19 pandemic. More details can be found in article number 2104495 by Mohan Edirisinghe and co‐workers.